The Influence of Green Marketing on the Purchase Intention of Green Fashion: A Study on the Brand “Sejauh Mata Memandang” - Najwa Syelby Tsurayya; Erlita Ridanasti (Indonesian Interdisciplinary Journal of Sharia Economics, 2025)
This study aims to analyze the influence of green marketing on the purchase intention of green fashion, using the brand “Sejauh Mata Memandang” as a case study. The research focuses on three main green marketing strategies: green advertising, green branding, and eco-labeling, as well as the role of consumer perception in green consumption. The research method employs a quantitative approach with purposive sampling, involving 247 respondents who are aware of and understand environmentally friendly fashion products from the brand. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that green advertising, green branding, and eco-labeling have a positive and significant influence on consumer perception. Furthermore, consumer perception also has a positive and significant impact on green consumption. These findings indicate that effective green marketing strategies can enhance positive consumer perceptions and encourage the purchase behavior of sustainable fashion products. The implications of this study provide strategic insights for fashion companies in developing environmentally friendly marketing approaches that can stimulate consumer purchase intention.